PHOTOMETRIC ANALYSIS OF PI OF THE SKY DATA - Opiela, R.; Malek, K.; Mankiewicz, L.; Siudek, M.; Sokolowski, Marcin; Zarnecki, A. (Ceske Vysoke Uceni Technicke, 2013)
Two fully automatic Pi of the Sky detectors with a large field of view, located in Spain(INTA) and in Chile (SPDA) observe the sky in search of rare optical phenomena, and also collectobservations which include many kinds of variable stars. To be able to draw proper conclusions fromthe data that is received, adequate quality of the detectors is very important. Pi of the Sky data aresubject to systematic errors caused by various factors, e.g. cloud cover seen as significant fluctuations inthe number of stars observed by the detector, problems with conducting mounting, a strong backgroundof the moon or the passage of a bright object, e.g. a planet, near the observed star. Some of theseadverse effects are already detected during cataloging of the individual measurements, but this is notsufficient to make the quality of the data satisfactory for us. In order to improve the quality of ourdata, we developed two new procedures based on two different approaches. In this paper we will saysome words about these procedures, give some examples, and show how these procedures improve thequality of our data.